1982
DOI: 10.1093/oxfordjournals.aje.a113498
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Cholera in Rural Bangladesh, 1966–1980

Abstract: Since 1963, the International Centre for Diarrhoeal Disease Research, Bangladesh (ICDDR,B), formerly the Cholera Research Laboratory, has maintained a field station in Matlab to treat patients from a surveillance population of 240,000 who have cholera and other diarrheal diseases. Since 1966, the authors have analyzed hospital records of 7141 surveillance-area patients culture-positive for v. cholerae 01 to relate the seasonality, age and sex distribution, and geographic trends with hypotheses concerning trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
214
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(224 citation statements)
references
References 0 publications
9
214
1
Order By: Relevance
“…Bangladesh, the number of cholera cases varies from year to year, but it flares into epidemics twice a yearonce in summer (March-April), and once in winter (September-December) (5,20). Vibrio cholerae survives in association with phytoplankton mainly blue green algae (7,8) and zooplankton (2,6).…”
mentioning
confidence: 99%
“…Bangladesh, the number of cholera cases varies from year to year, but it flares into epidemics twice a yearonce in summer (March-April), and once in winter (September-December) (5,20). Vibrio cholerae survives in association with phytoplankton mainly blue green algae (7,8) and zooplankton (2,6).…”
mentioning
confidence: 99%
“…For example, through research on seasonality and phage typing in Bangladesh, Glass et al (1982) According to Islam et al (1994) there are two types of environmental reservoirs that support the survival of V. cholerae in its association with blue-green algae: temporary and permanent. Temporary reservoirs are considered to be closed water systems (i.e., ponds and tanks), which help the pathogen to spread throughout the hwnan population by way of seasonal multiplication ofalgae bloom (Islam et al 1994).…”
Section: Cholera Ecologymentioning
confidence: 99%
“…The peak season for EI Tor usually occurs between September and December. For both cholera biotypes, a small peak occurred in the pre-monsoon months of March through June (Glass et al 1982). Longini et al (2002) studied cholera trends over a 33 year period in Bangladesh and found that despite the year to year fluctuations in cholera rates, the timing of the pre-and post-monsoon epidemics remain the same, regardless of the organism's biotype.…”
Section: Cholera and Seasonalitymentioning
confidence: 99%
See 2 more Smart Citations